THU0287 Glucocorticoids Withdrawal in Systemic Lupus Erythematosus: Myth O Reality?. (15th July 2016) - Tani, C.; Carli, L.; Vagelli, R.; Signorini, V.; Vagnani, S.; Totti, D.; Tristano, M.; Mosca, M.
Abstract : Background: Glucocorticoids (GC) minimization is a pursued goal in the management of systemic lupus erythematosus (SLE) and is a target in patients (pts) management [1]. However, real-life data show that the vast majority of SLE pts are receiving long-term GC therapy despite being considered in clinical remission by their treating physician [2]. Few data are available on treatment discontinuation and tapering protocols in routine clinical practice. Objectives: To analyze the clinical characteristics and the disease outcome of a group of GC free SLE pts Methods: GC-free SLE pts were selected from the lupus clinic database; this is an electronic database where demographic, clinical and serological data, as well as therapies of patients referring to the clinic, are prospectively collected and regularly updated. Disease activity is defined by the clinician's judgement as well as by the SELENA-SLEDAI and the ECLAM scores, damage accrual is computed according to the SLICC-DI score. Results: Out of 410 pts followed at the clinic, 210 had a regular follow-up (at least 3 yearly assessments) and were included in the study. Out of these, 46 (21.9%) pts were GC free for at least 3 months and were included in the present analysis. Forty-one (89%)were female and the mean age at enrolment was 43.3±13; 16 pts had a history of lupus nephritis (35%). At the last visit, the median duration of GC withdrawal was 24 months (3–141 months) and 84% were GC free for at least 12 months. Thirty-eight pts (82.6%) were taking antimalarials, 32 patients were also immunosuppressant free.At GC stopping, mean disease duration was 11.6±8 years (2 to 35), being less than 5 years in 17%; 21 patients (46%)were in clinical and serological remission, 23 (50%) had serological activity (low complement and/or anti-dsDNA), 2 (4%) had mild hematological abnormalities. Organ damage (SLICC≥1) was present in 12 pts (26%). After GC withdrawal, disease flares were observed in 8 pts (17%): one severe flare (lupus nephritis onset), 7 minor flares (3 articular, 2 cutaneous, 2 hematological) requiring a short course of GC therapy. Additionally, shortly after GC stopping, fatigue was reported by 3 pts. Interestingly, only two pts (4.3%) accrued further damage during the follow-up (cancer and coronary artery disease) over a period of 60 and 72 and months respectively. No differences in patients' age, disease duration, disease activity or ongoing therapies at GC stopping were observed between pts who flared vs those without flares. Additionally, serological activity at GC withdrawal was not associated with an increased risk of disease flare. Conclusions: In our cohort GC withdrawal was successfully attempted in 20% of cases. A severe flare was observed in only one patient; interestingly, a very low damage accrual was recorded. No clinical or serological variables predictive of disease flare after GC stopping were identified. Our data support that GC withdrawal is an achievable goal in SLE patients in routine clinical practice and represent a feasible target in the disease management. References: van Vollenhoven RF et al. Treat-to-target in systemic lupus erythematosus: recommendations from an international task force. Ann Rheum Dis. 2014 Jun;73(6):958–67. Schneider M et al. Understanding remission in real-world lupus patients across five European countries. Lupus. 2015 Dec 2. Disclosure of Interest: None declared